Science, Technology, Engineering, Arts, and Mathematics Learning with Loose Parts to Foster Early Childhood Creativity in Islamic Educational Institutions - Asmidar Parapat; Munisa Munisa; Rita Nofianti; Saputri Wulandari (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
The development of creativity in early childhood within many Islamic educational institutions remains suboptimal because learning tends to be teacher-centered, offers limited exploration, and provides insufficient play experiences that stimulate higher-order thinking. This condition is also evident at Nurul Qur’an Stabat Kindergarten, where children have not yet gained adequate opportunities to experiment and generate original ideas. This study aims to examine how the implementation of STEAM-based learning (Science, Technology, Engineering, Arts, and Mathematics) using Loose Parts can enhance early childhood creativity. The research employed a qualitative method with a descriptive approach through observation, interviews, and documentation. The findings show that the use of Loose Parts in STEAM-based learning successfully improved children’s creative thinking abilities, particularly in problem-solving, innovation, flexibility, and the ability to generate new ideas. Children became more active, imaginative, and confident in expressing their thoughts. These results indicate that the integration of STEAM and Loose Parts is not only effective in fostering creativity but also relevant for enriching learning practices in Islamic educational institutions that aim to develop children’s potential holistically.